2004
DOI: 10.1017/s0959269504001826
|View full text |Cite
|
Sign up to set email alerts
|

Research on form-focused instruction in immersion classrooms: implications for theory and practice

Abstract: This article presents a comparative analysis of five quasi-experimental studies involving close to 1,200 students, ranging in age from 7 to 14, in 49 French immersion classrooms in Canada – a content-based instructional context where learners develop high levels of communicative ability yet demonstrate a levelling-off effect in their grammatical development. The studies investigated the effects of form-focused instruction on four areas known to be difficult for anglophone learners of French: perfect vs. imperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 48 publications
3
38
0
4
Order By: Relevance
“…According to experts, grammar still holds a central position in language teaching (R. Ellis, 2006) and may foster more subconscious FL learning and improve learners' interlanguage (Nassaji, 2000;Norris & Ortega, 2000;Doughty, 2003;Robinson, 2003;Lyster, 2004a;Lyster, 2004b;R. Ellis, 2006;Klapper, 2006;Dörnyei, 2009).…”
Section: The Notions Of Implicit/explicit In Grammar Instructionmentioning
confidence: 99%
“…According to experts, grammar still holds a central position in language teaching (R. Ellis, 2006) and may foster more subconscious FL learning and improve learners' interlanguage (Nassaji, 2000;Norris & Ortega, 2000;Doughty, 2003;Robinson, 2003;Lyster, 2004a;Lyster, 2004b;R. Ellis, 2006;Klapper, 2006;Dörnyei, 2009).…”
Section: The Notions Of Implicit/explicit In Grammar Instructionmentioning
confidence: 99%
“…In other words, it does not interrupt learners' conversation (Oliver, 1995;Long, 1996;Doughty & Varela., 1998;Doughty, 2001;Leeman, 2003). The smaller effect of recasts might be due to the ambiguity it produces for the students in a way that might make them confused between whether the teacher's feedback was an indication of confirmation or a disapproval feedback on their output (Lyster, 2004). Analyses of the errors showed that Kurdish-Arabic L3 learners of English were least accurate on IDS context, because the source of the errors was substitution rather than omission.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies show that there was no significant difference among different feedback types (e.g., Ammar & Spada, 2006;Loewen & Nabei, 2007;McDonough, 2007), others uncovered different effects of diverse types of feedback on L2 development (e.g., Long, Inagaki, & Ortega, 1998;Leeman, 2003;Ellis, Loewen, & Erlam, 2006). Many studies have examined the advantages of prompts in comparison with that of recasts (e.g., Yang & Lyster, 2010;Havranek, 1999;Ellis, Loewen, & Erlam, 2006;Lyster, 2004;Ammar & Spada, 2006). While the research studies in the classroom usually show prompt as more beneficial, laboratory studies suggest that recasts have a facilitating effect on the development of the second language.…”
Section: Prompts and Recastsmentioning
confidence: 99%
See 2 more Smart Citations